Respostas
respondido por:
1
resolução!
a1 = x - 9
a2 = x
a3 = 3x + 12
( a2 )^2 = ( a1 ) ( a3 )
( x )^2 = ( x - 9 ) ( 3x + 12 )
x^2 = 3x^2 + 12x - 27x - 108
3x^2 - x^2 + 12x - 27x - 108 = 0
2x^2 - 15x - 108 = 0
∆ = (-15)^2 - 4 * 2 * (-108)
∆ = 225 + 864
∆ = 1089
X ' = 15 + √∆ / 4
X ' = 15 + √1089 / 4
X ' = 15 + 33/4
X ' = 48/4
X ' = 12
X " = 15 - 33/4
X " = - 18/4
X " = - 9/2
= x - 9 , x , 3x + 12
= 12 - 9 , 12 , 36 + 12
= 3 , 12 , 48
PG = { 3 , 12 , 48 }
resposta : X = 12
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás